#TITLE_ALTERNATIVE# - INDRA BASHKARA (NIM : 12405015), NICKO
Subsurface imaging using seismic methods must take into account the slope factor of the reflector. Too steep angle of the reflector causing the reflector difficult to imaged. In conventional seismic method, the reflector is assumed as a point, while the method of the Common Reflection Surface (CRS) assume that the reflector is an area that is equal Fresnel zone. Both methods were tested to imaging reflectors that steeply sloped. Fresnel zone used by the CRS is calculated based on the assumption of flat layers. Fresnel zone is a function of wave frequency and velocity layers. Use some kind of frequency were intended to find the right parameters on the method of CRS to imaged reflector which has a steep slope. From the experiments conducted, the results of the CRS stack is not better when imaged reflectors which has a steep slope compared with results of conventional methods. This is due to the assumption of Fresnel zone calculations on a flat layer is not appropriate when applied to the sloping layer. But the RMS velocity results from the CRS velocity analysis method showed better results than conventional methods. Therefore, this velocity is used as input in the process of conventional stacking.